DEVELOPMENT OF STEM-ORIENTED CREATIVE CONTENT BASED ON ELECTRONIC PORTFOLIO IN CHEMISTRY LEARNING - Nahadi Nahadi; Wiwi Siswaningsih; Dini Dwi Apriani; Pupung Purnawarman; Hayuni R. Widarti; Ari S. Shidiq; Triannisa Rahmawati; Atep R. Nurhadi; Qurrotu A. Zahran (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to develop a STEM-oriented creative content based on electronic portfolio assessment instrument to improve students' critical thinking skills on buffer solution material. The assessment instruments developed were tasks and rubrics. The research was conducted using the research and development method 4D model and was carried out in only three stages, namely define, design, and develop, with limited trials. The research instruments used were interview guidelines, validation sheets, observation sheets, tasks, and rubrics. The participants in this study is XI class students. The tasks developed in this electronic portfolio assessment consisted of three tasks: analysis essay questions, summaries, and practicum reports. The results showed that the instrument was valid and reliable. Based on the results of the limited trial, the electronic portfolio assessment instrument developed can improve students' critical thinking skills on buffer solution material with moderate and high classifications.